Debted Objects: Homemaking in an Era of Mortgage-Enabled Consumption - Cook, N.; Smith, Susan; Searle, B. (Routledge, 2013)
This paper assesses the relevance of mortgage-led consumption for the assemblage of home. Drawing on qualitative research completed in the UK, we show how the materials and meanings of owner-occupation are constituted by, and experienced through, the accumulation and deployment of secured debt. This is enabled by a particular financial regime, in which the proceeds of equity borrowing are freed for discretionary expenditure. Homes and their contents thus acquire the status of 'debted objects', and these form an interface between the financial and familial values comprising residential space. By attending to these mortgage-enabled purchases, we expose and evaluate the myriad ways in which equity borrowings animate the assemblage of home, adding value to property, linking domestic space with distant geographies and inspiring the art of dwelling. © 2013 Copyright Taylor and Francis Group, LLC.